Effect of feeding graded levels of Leucaena leucocephala, Leucaena pallida, Sesbania sesban and Chamaecytisus palmensis supplements to teff straw given to Ethiopian highland sheep - Kaitho, R.J.; Umunna, N.N.; Nsahlai, I.V.; Tamminga, S.; Bruchem, J. van (Elsevier, 1998)
The effect of feeding Leucaena leucocephala, Leucaena pallida, Sesbania sesban and Chamaecytisus palmensis supplements on intake, digestibility and liveweight changes was evaluated using 102 male Ethiopian highland sheep in a 90-day trial. Teff straw (Eragrostis tef) was fed ad libitum (control diet), or supplemented with 15, 30, 45 or 60 of ration DM intake of L. leucocephala, L. pallida, C. palmensis or S. sesban in a randomized complete block design. There was a decrease (P<less than>0.05) in teff straw intake as the level of supplement increased. Substitution rates (g/kg supplement) increased with increasing levels of supplementation. Substitution rate varied from 162 to 528 in L. pallida, <minus>89 to 312 in L. leucocephala, <minus>566 to 231 in S. sesban and <minus>10 to 134 in C. palmensis supplemented diets. DM and digestible organic matter intake increased (P<less than>0.05) with increasing L. leucocephala, C. palmensis and S. sesban, but not L. pallida. Liveweight gain increased (P<less than>0.01) with increasing level of browse supplementation. Sheep fed the control diet lost weight (<minus>24.4 g/day) while the supplemented ones gained weight in the range of 6.5-65.2 g/day. The maximum liveweight gain (65.2 g/day) was observed in sheep fed a diet with 60 L. pallida. The optimum levels of browse supplementation in terms of liveweight gain per g supplement were 45, 45, 30, 30 DM of total ration for L. leucocephala, L. pallida, C. palmensis and S. sesban, respectively. A close relationship between liveweight gain and amount of supplement was observed. The digestibilities of DM, organic matter, N and supplement DM increased (P<less than>0.05) with increasing level of supplementation. There were no differences in NDF digestibility. Faecal N, urinary N output and N retention increased (P<less than>0.0001) with level of supplementation.